Comprehensive multiomics analysis of the effect of ginsenoside Rb1 on hyperlipidemia - Lianqun, Jia (Aging (Albany NY), 2021)
We analyzed the effects of ginsenoside Rb1 on hyperlipidemic in model mice. Using stool, plasma and hepatic tissue samples, we observed that the genera Blautia and Allobaculum were increased and Turicibacter was decrease in Rb1-treated mice as compared to untreated model mice. Ether lipid metabolism, glycerolipid metabolism, and glyoxylate and dicarboxylate metabolism were differentially enriched between the Rb1 and model groups. Lipidomics revealed 169 metabolites differentially expressed between the model and Rb1 groups in a positive ion model and 58 in a negative ion model. These metabolites mainly participate in glycerophospholipid, linoleic acid, and alpha-linolenic acid metabolism. The main metabolites enriched in these three pathways were phosphatidylcholine, diacylglycerol and ceramide, respectively. In a transcriptome analysis, 766 transcripts were differentially expressed between the Rb1 and model groups. KEGG analysis revealed lysine degradation, inositol phosphate metabolism, and glycerophospholipid metabolism to be the main enriched pathways. Multiomics analysis revealed glycerophospholipid metabolism to be a common pathway and phosphatidylcholine the main metabolite differentially enriched between the Rb1 and model groups. Results from fecal transplanted germ-free mice suggest that to suppress hyperlipidemia, Rb1 regulates gut microbiota by regulating the synthesis and decomposition of phosphatidylcholine in glycerophospholipid metabolism, which in turn decreases serum total cholesterol.